2011
DOI: 10.1111/j.1460-9592.2011.03534.x
|View full text |Cite
|
Sign up to set email alerts
|

Predicting weight using postmenstrual age – neonates to adults

Abstract: Summary Objectives:  To describe the pattern and variability of body weight with postmenstrual age (PMA) using nonlinear mixed effect modeling and to create a single mathematical function that can be used from prematurity to adulthood. Background:  PMA has been shown to predict functional properties of humans such as glomerular filtration rate and drug clearance. Widely used growth charts use postnatal age to predict weight in an idealized population and are not available as a mathematical function. Methods:  … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…Sumpter and Holford previously used a Hill-type function to describe body weight and postmenstrual age relationship in premature neonates, infants, children, and adults (15). However, with this approach using the CDC and WHO datasets and adding 9 months to adjust from postnatal age to postmenstrual age, their equation did not quite capture the overall variability of the CDC dataset (Fig.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Sumpter and Holford previously used a Hill-type function to describe body weight and postmenstrual age relationship in premature neonates, infants, children, and adults (15). However, with this approach using the CDC and WHO datasets and adding 9 months to adjust from postnatal age to postmenstrual age, their equation did not quite capture the overall variability of the CDC dataset (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…1 of Sumpter and Holford (15) was used to simulate 10,000 age-matched weights in pediatric population (gestational age between 0 and 18 years). The interindividual variability was characterized by an exponential model.…”
Section: Simulation Of Sumpter and Holford Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the problem with using post-natal age has been raised in that post-natal age is less likely to reflect a continuous growth process in the pediatric population, particularly in pre-term to infant babies, and less likely to correlate with PK parameters than using post-menstrual age. [6,7] Hence, there are suggestions of using PMA instead of post-natal age when growth or organ maturation is considered. In line with this suggestion, PMA was used in our analysis, which demonstrated that average weights of new born babies were different for different PMA groups despite being in the same postnatal age group.…”
Section: Discussionmentioning
confidence: 99%